Partnership development of smallholder coffee cultivation: A model for social capital in the global value chain - Adi Haryono; Ina Juniarti; Karjo Matajat; Arif Imam Suroso; Moelyono Soesilo (Economies, 2024)
The productivity of smallholder coffee cultivation is declining due to ageing trees, making the rejuvenation of coffee trees with superior seeds essential. This rejuvenation process requires the support and participation of various stakeholders, including the government, banks, investors, universities, community leaders, experts, extension workers, and other parties. The nature of an incomplete contract in building partnership with farmers requires confidence building to avoid higher costs in enforcing a new behavior. However, this study shows that the accumulation of social capital also leads to higher expenses in maintaining these relationships. This study aimed to develop a social capital model to enhance partnerships between coffee farmers and relevant stakeholders. The analysis used a system dynamics model for coffee production and farmer income. The data collection involved the gathering of data and information from 17 actors in the coffee industry in Lampung, particularly in Kopista community. The study reveals that the social capital model must be constructed from four components: (1) trust, (2) ongoing cooperative activities, (3) social capital connections, and (4) memories of successful cooperative actions. Active involvement and instruction from specialists on the concept of social capital and partnership models can enhance cooperation by maintaining social connections. The policy implication of this study is that the development of a social capital model and partnership must be constructed by mentoring for economic benefits and must be continuously supported.
Keywords: 330; coffee; contract farming; incomplete contract; partnership; social capital